L4 fixation is not necessary in L5-Iliac spinopelvic fixation after trauma, but coadjutant transilio-transsacral fixation is - Sevillano-Pérez, Enrique; Prado-Novoa, María; Postigo-Pozo, Sergio; Peña Trabalón, Alejandro; Guerado-Parra, Enrique (Elsevier, 2024)
Introduction: Spinopelvic dissociation (SPD) is a severe injury characterized by a discontinuity between the spine and the bony pelvis consisting of a bilateral longitudinal sacral fracture, most of the times through sacral neuroforamen, and a horizontal fracture, usually through the S1 or S2 body. The introduction of the concept of triangular osteosynthesis has shown to be an advance in the stability of spinopelvic fixation (SPF). However, a controversy exists as to whether the spinal fixation should reach up to L4 and, if so, it should be combined with transiliac-transsacral screws (TTS). Objective: The purpose of this study is to compare the biomechanical behavior in the laboratory of four different osteosynthesis constructs for SPD, including spinopelvic fixation of L5 versus L4 and L5; along with or without TTS in both cases. Material and methods: By means of a formerly described method by the authors, an unstable standardized H-type sacral fracture in twenty synthetic replicas of a male pelvis articulated to the lumbar spine, L1 to sacrum, (Model: 1300, SawbonesTM; Pacific Research Laboratories, Vashon, WA, USA), instrumented with four different techniques, were mechanically tested. We made 4 different constructs in 5 specimen samples for each construct. Groups: Group 1. Instrumentation of the L5-Iliac bones with TTS. Group 2. Instrumentation of the L4-L5-Iliac bones with TTS. Group 3. Instrumentation of L5-Iliac bones without TTS. Group 4: Instrumentation of L4-L5-Iliac bones without TTS. Results and conclusions: According to our results, it can be concluded that in SPD, better stability is obtained when proximal fixation is only up to L5, without including L4 (alternative hypothesis), the addition of transiliac-transsacral fixations is essential.
Keywords: Sacro (Hueso) - Fracturas; Fractures of the sacrum; Iliosacral screw; Lumbopelvic dissociation; Pelvic fixation; Sacral fractures; Spinopelvic dissociation; Spinopelvic fixation; Spinopelvic stabilization; Transiliac-transsacral screw; Triangular osteosynthesis